Antioxidant and antimicrobial activities of sustainable Salvia hispanica L. seed extracts against gram-positive and gram-negative bacteria - Hadef, Khawla; Attou, Amina; Madjidi, Nour (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Salvia hispanica L. (chia) seeds are rich in bioactive compounds with antioxidant and antimicrobial properties, making them valuable natural ingredients for food and agro-industrial applications. Food contamination by Gram-positive and Gram-negative bacteria remains a major challenge for food safety, highlighting the need for sustainable natural preservatives. This study aimed to compare two green extraction methods for recovering bioactive compounds from Algerian dark chia seeds and to evaluate the antioxidant and antimicrobial activities of the resulting extracts against Gram-positive and Gram-negative bacteria. Aqueous Soxhlet extraction and ethanolic maceration were applied. Extracts were analyzed for total phenolics and flavonoids, antioxidant activity (DPPH assay), and antimicrobial activity using the disc diffusion method against nine microbial strains, including Gram-positive and Gram-negative bacteria and Candida albicans. The aqueous Soxhlet extract exhibited the highest total phenolic content and strong antioxidant activity (88 % DPPH inhibition at 400 μg.mL-1). The ethanolic maceration extract was richer in flavonoids and showed moderate, dose-dependent antimicrobial activity. Gram-positive bacteria (Staphylococcus aureus and Listeria monocytogenes) were most sensitive (up to 12 ± 1 mm), while Gram-negative bacteria were generally more resistant, except Klebsiella pneumoniae (15 ± 1 mm at 15 mg.mL-1). Candida albicans was highly susceptible (14 ± 1 mm). Green-extracted chia seed extracts demonstrate significant antioxidant and moderate antimicrobial activities, supporting their potential use in food preservation, sustainable product development, and eco-friendly agro-industrial applications.